Pengembangan Model Sistem Informasi Geografis Angkot Online Berbasis SCRUM: Ujicoba Kelayakan - Rifa’i, Mochamad Fikri; Ghazali, Dexsa Muliana; Riyan, Ade Bani (Building of Informatics, Technology and Science (BITS), 2022)
Angkot drivers can compete with online transportation in getting passengers via smartphones. This application is based on a geographic information system, which is a system that can show the location of a person or place online, using this system to be integrated with public transportation makes it possible to add or pick up passengers more efficiently not only by waiting in one place but can pick up passengers according to the location of the passenger and the transportation route. To overcome the above problems, making applications with a technology theme is one of the right solutions for innovative methods that will be applied to public transportation drivers so they can get passengers efficiently. The purpose of this study is to determine the user's response to the application that has been developed. The research method used is research and development with a 4D development model with “define, design, development, and dissemination stages”. Data collection was carried out by distributing questionnaires to several respondents, while the trial stages carried out included alpha version trials, beta versions trials, Version Release, and Implementation. The results of the study show that the indicators of language, appearance, and accessibility of applications that have been developed are classified as "very feasible". The developed online angkot application is expected to be a solution in dealing with technological developments that can be applied to public transportation